Policies for stronger productivity growth in Latvia - Yashiro, Naomitsu (OECD Economics Department Working Papers, 2019)
Latvia's productivity growth is held back by weak innovation and inefficient resource allocation. The shortage of skilled workers which constrains innovation and the adoption of digital technologies must be addressed through further alignment of vocational and tertiary education with labour market demand. Strengthening the innovation ecosystem by improving the quality of research and collaboration between firms and research institutions would help to diffuse digital technologies more widely across the economy. Fighting widespread informality, improving the low debt recovery through a more efficient insolvency regime, and reducing substantial state ownership would improve the allocation of resources. Latvia also relies heavily on EU funds to finance its important structural policies. The continuity of the most effective EU funded policy instruments needs to be ensured in the medium term, by integrating them into the national budget. This Working Paper relates to the 2019 OECD Economic Survey of Latvia (http://www.oecd.org/economy/surveys/latvia-economic-snapshot/)